(untitled) (Journal of Medical & Health Sciences Review, 2025)
The purpose of this study was to observe the significant difference between diabetic and non-diabetic oral situations based on Gingival Index (GI) and Calculus Index (CI) to gain a clear idea about the effect of diabetes in periodontal health. Diabetes mellitus (DM) is associated with increased gingival inflammation and greater calculus accumulation due to its association with periodontal disease. The GI scores gingival inflammation and the CI gives the tooth surface scoring (extent of calculus) which are parameters of periodontal health. Clinical examination was done in this cross sectional study in the 100 participants with 50 diabetic and 50 non diabetic individuals. The GI and CI were used to record the severity of gingival inflammation and calculus deposits. The diabetic patients were significantly more GI and CI scores than non diabetic patients and showed severer periodontal disease. Results indicate a risk of greater periodontal complications among diabetic patients and underscore the clinical importance that more aggressive preventive and therapeutic periodontal care be used to benefit the diabetic patient. However, the study is a valuable source of information as regards the relationship between diabetes and oral health and the requirement for the inclusion of oral health management in diabetic patients’ overall care.